2018
DOI: 10.1007/s11442-018-1483-z
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich mapping of rodent density in Jilin Province, China

Abstract: Rodents are the main host animals that spread plague, and Spermophilus dauricus (S. dauricus) is the most common rodent in North China. In this study, a rodent density survey was carried out in China's Jilin Province from April to August 2005. Moran's I and semivariogram curves were used to investigate the spatial distribution characteristics of the sampling data. We found that the spatial auto-correlation index was low and failed to generate a meaningful semivariogram curve. In this case, commonly used interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Secondly, the results of discretization should be as suitable as possible for the subsequent models. If we arbitrarily discretize continuous data before modelling, the subsequent analysis and application may miss valuable information or lead to misspecification of models, e.g., Boolean networks (Kauffman, 1969), generalized logical networks (Song et al, 2009), or Sandwich Interpolation model (Wang et al, 2002(Wang et al, , 2013Liu et al, 2018). Therefore, the effectiveness of the discretization algorithm is not only related to discrete data distribution, but also related to the subsequent application models.…”
Section: Discretization Methods For Continuous Datamentioning
confidence: 99%
“…Secondly, the results of discretization should be as suitable as possible for the subsequent models. If we arbitrarily discretize continuous data before modelling, the subsequent analysis and application may miss valuable information or lead to misspecification of models, e.g., Boolean networks (Kauffman, 1969), generalized logical networks (Song et al, 2009), or Sandwich Interpolation model (Wang et al, 2002(Wang et al, , 2013Liu et al, 2018). Therefore, the effectiveness of the discretization algorithm is not only related to discrete data distribution, but also related to the subsequent application models.…”
Section: Discretization Methods For Continuous Datamentioning
confidence: 99%
“…Besides the above two case studies, Liu et al (2018) tested the SSH and SAC of rodent density in a study area, and they found that the former is significant and the latter is weak. Then, both the SSH-based Sandwich estimator (Wang et al, 2013a) and SAC-based kriging were applied to the same sample to map the population, respectively.…”
Section: Climate Datasetmentioning
confidence: 99%
“…This study uses the Sandwich mapping model, which is based on the SSH property, to compute the values of the reporting units by propagating the means of the homogeneous strata to the intersecting reporting units (Wang et al, 2013). Even when the SAC is weak or absent, the Sandwich model allows for the creation of reliable predicted surfaces (Liao, Li, Zhang, Xia, et al, 2018; Liu et al, 2018; Yang et al, 2017). Another advantage of the Sandwich model is that it considers the stratification of heterogeneity that is independent of the reporting units; therefore, each stratum can contain samples that fall outside of its intersecting reporting units (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%